Benthic Communities on the Mohn’s Treasure Mound: Implications for Management of Seabed Mining in the Arctic Mid-Ocean Ridge - Ramirez-Llodra, Eva; Hilario, Ana; Paulsen, Emil; Costa, Carolina Ventura; Bakken, Torkild; Johnsen, Geir; Rapp, Hans Tore (Frontiers in Marine Science, 2020)
The Mohn’s Treasure, described as an inactive sulphide mound, was discovered at 2600 m depth on the Arctic Mid-Ocean Ridge in 2002. In 2015, we conducted the first biological survey of Mohn’s Treasure using ROV photo transects and sampling. This site is covered by a thick layer of fine sediments, where hard substratum is only visible as rocky outcrops on ridges. The observed benthic community was typical of Arctic bathyal systems. A total of 46 species (identified as morphospecies) were recorded, with densities varying from 12.2 to 31.6 ind.m-2. The two most abundant phyla were Porifera and Echinodermata. The sediment is dominated by fields of the stalked crinoid Bathycrinus carpenterii, while areas of hard substratum were characterised by high abundances of several sponge species and associated fauna. Interest in commercial exploration and exploitation of minerals from massive sulphide deposits is rising globally, and the Arctic Mid-Ocean Ridge is being targeted for mineral exploration within Norwegian waters. Gathering baseline ecological data from these poorly known sites is thus urgent and essential if robust resource management measures are to be developed and implemented. The results of this ecological survey are discussed in relation to the designation of deep-sea Vulnerable Marine Ecosystems and their implication in management and conservation of areas targeted by the emerging deep-sea mining industry.